Contradictions in Chilean public education policy: physical education and health case - Reyes Rodríguez, Alixon David; Martínez Rojas, Ezequiel (Frontiers in Sports and Active Living, 2024)
The purpose of this text is to point out the contradiction existing in Chilean educational public policy regarding the curricular reform that converted the subjects of Physical Education and Health, History, Arts, and Religion into optional subjects for the 3rd and 4th years of high school. As far as Physical Education is concerned, scientific evidence shows that such conversion to the status of optional subject goes against the policies of other executive ministries and against the possibilities of reversing the statistics that show Chile as one of the countries in America with the highest percentage of overweight and obese children and adolescents.